STUDI POLA RUANG LUAR PADA KEGIATAN BUDAYA DI HUTA SIALLAGAN - B, Yeremia Jodie; Silitonga, Shanty; Aritonang, Emmy Ria (ALUR :Jurnal Arsitektur, 2019)
The society of Batak Toba in Huta Siallagan has customs inherited by their ancestors, where there are customs and cultural patterns in the outer space including cultural ceremonies, customs and traditions. Based on the phenomenon found in the tourist village of Huta Siallagan, the researcher examines a culture pattern that has been formed and has its own attraction in the form of cultural tourism that makes it as one of tourism assets based on the potential of rural areas. Qualitative descriptive research strategy is where qualitative research is rooted in the natural setting as a whole, relying on human as a research tool, utilizing qualitative methods and conducting inductive data analysis. Qualitative research is concerned with the process rather than results. Desiring the limits of the research on the basis of the focus that arises as a problem, has a set of criteria for measuring the validity of data through agreement between the researcher and the subjects studied and descriptive studies trying to describe and interpret what is and can be about the conditions or relationships that exist, , ongoing processes, effects, or growing trends. Descriptive studies are primarily concerned with the present, although it is not uncommon to take into account past events and their effects on current conditions on the pattern of outer space on cultural activities occurring in Huta Siallagan